1990
DOI: 10.1139/v90-213
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR studies of the conformational mobility of 1,2-dimethoxybenzene in solution

Abstract: . Can. J. Chem. 68, 1393 (1990). IH NMR and 13C NMR spectral data are presented for 1,2-dimetho~~benzene-a,a'-~~C, as well as for a number of other anisole derivatives. For the title molecule, the coupling constants between the I3C nucleus in the side chain and the para ring proton or 13C nucleus in the benzene ring show that the expectation value of sin2 8 is very near 0.2 at 300 K, where 8 is the angle by which the methoxy groups twist out of the aromatic plane. This value of (sin2 8) is much larger than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…18 Since the benzenoid ring is important for inhibitory activity, the role of the dimethoxy substituents on this ring should be questioned. Desmethoxyquinazoline derivatives (34-37) were found to be far less active against G9a, which is in agreement with a recent report on related analogues, [35][36][37][38][39][40][41][42] and demonstrates that these substituents are also of importance. A number of theoretical and experimental studies have shown that orthodimethoxybenzenes prefer to adopt a co-planar conformation, with the sp 2 oxygen lone pairs projecting towards each other and the corresponding methyl groups angled away from each other.…”
Section: Resultssupporting
confidence: 89%
“…18 Since the benzenoid ring is important for inhibitory activity, the role of the dimethoxy substituents on this ring should be questioned. Desmethoxyquinazoline derivatives (34-37) were found to be far less active against G9a, which is in agreement with a recent report on related analogues, [35][36][37][38][39][40][41][42] and demonstrates that these substituents are also of importance. A number of theoretical and experimental studies have shown that orthodimethoxybenzenes prefer to adopt a co-planar conformation, with the sp 2 oxygen lone pairs projecting towards each other and the corresponding methyl groups angled away from each other.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies have explored the conformations of the structural analogue ODMB in different organic solvents. Authors have reported the solvent dependence of planarity versus nonplanarity of ODMB in low-temperature glasses and in the liquid phase. However, the experimental reports leave it unclear whether nonplanarity implies only a temporary departure from planarity within the basin centered at the planar minimum, or whether, like in the gas phase, stable nonplanar conformers exist. To the best of our knowledge, there are no published data for the conformer populations of ODMB in the aqueous phase.…”
Section: Resultsmentioning
confidence: 99%
“….n(O) interactions between the two methoxy groups. However, from the data available in the literature the coplanar arrangement seems to be the most stable, which would mean that ultimately mesomeric stabilization determines the observed conformations [27][28][29][30][31][32]. In contrast, it is conceivable that this mesomeric stabilization will change when methoxy groups are moved to other positions on the benzene ring or when more methoxy groups or other mesomerically active groups are introduced.…”
Section: Introductionmentioning
confidence: 99%